Weak State Sebagai Sebuah Ancaman Keamanan: Studi Kasus Kolombia - Herningtyas, Ratih (Universitas Muhammadiyah Yogyakarta, 2014)
This paper aims to describe how a weak state can become a threat to the security of other countries, using Colombia as a case study. Colombia showed a weak state characteristic as seen from the lack of control and the existence of government, military capabilities are limited, dysfunctional judicial system and weak law enforcement, as well as a weak tax collection system. The condition was successfully exploited by drug trafficking organizations to operate as well as deploy a security threat not only for the internal region of Colombia, but also for other nations. The existence of Colombia as a weak state and successfully exploited by drug trafficking organizations causing security threats such as terrorism, weapons proliferation and environmental degradation.